KECERDASAN EMOSIONAL INTRAPERSONAL PADA ANAK USIA 5 TAHUN YANG MENGALAMI BULLYING (STUDI KASUS DI TAAM AR-RIDHO) - Fatimah Nur Annisa, - (2022)
This research is based on the surrounding phenomenon and the views of the surrounding community regarding the emotions of children who are victims of bullying. The purpose of this study is to describe the intrapersonal emotional intelligence of children aged 5 years who are experiencing problems at TAAM Ar-Ridho. The approach used in this research is a qualitative case study design with the subject of group B students of TAAM Ar-Ridho experiencing problems. The data collected by the researcher used observation, interview, and documentation techniques. Then obtain the data to be obtained analyzed with analytical techniques using data reduction steps, data display, and draw conclusions. In testing the validity of the data using a credibility test with triangulation, reference materials, and member checks. The results showed that from the aspect of the ability to regulate self-emotions according to the situation and condition, the child could not delay feeling happy, tended to cry and scream if the situation and conditions were not in accordance with his wishes. From the aspect of the ability to utilize self-emotions positively, the child has been able to express his desires more expressively and actively in interacting, sometimes he often pranks his friends or is pranked by his older friends. In terms of self-defense in dealing with problems, the way he faces problems by fighting physically and nonphysically which sometimes he becomes a victim of bullying at school, the child is also able to take responsibility when he has self-awareness of himself and his environment.